Predictors of Interventional Treatment Use for Venous Thromboembolism in Cancer Patients. (13th September 2016) - Yoon, Lara; Clarke Hillyer, Grace; Chen, Ling; Hu, Jim C.; Neugut, Alfred I.; Hershman, Dawn L.; Wright, Jason D.
ABSTRACT: Venous thromboembolic disease is a major cause of morbidity in cancer patients. The Perspective database was used to identify patients with solid tumors and a diagnosis of VTE from 2006 to 2012. We examined use of IVC filters, thrombolysis, and thrombectomy. Among 32, 545 patients, 23.1% received an IVC filter, 1.9% thrombolytic therapy, and 0.4% underwent thrombectomy. Use of IVC filters decreased between 2006 and 2012 (23.4% to 21.2%, p = 0.012). Older patients, uninsured patients, Hispanics, and those with more comorbidities were more likely to undergo filter placement while patients at rural hospitals were less likely to receive an IVC filter ( p < 0.05 for all).